Family poultry development systems among smallholder broiler farmers in the Goromonzi district of Zimbabwe. Issue 4 (8th August 2021) - Kamoyo, Michael; Guta, Portia Fadzai
ABSTRACT: This paper analyzes the dynamics at play in community poultry projects in Zimbabwe. We compare the performance levels of "family poultry" under three community-based development schemes: the contract-based scheme and the two community-led poultry development approaches, one supported by an NGO and the other under self-funding. Factors that influence farmers' choice of the poultry scheme are also determined. Data was collected using observations and self-administered questionnaires from 61 smallholder poultry farmers in the Goromonzi District. Results indicate that landholding and distance to the nearest urban center influence the farmers' choice of poultry scheme and that no single scheme is superior to the other. While the contract-based scheme records the highest sales and bird per cycle, it undermines the community's capabilities to act independently. Contractors control price, marketing, and genetic-type decisions. In contrast, the other approaches have lower material returns, but they build the community's broad-based capabilities for self-improvement.